2016
DOI: 10.1186/s40064-016-3114-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of preoperative MRI and intraoperative findings of posterior tibial tendon insufficiency

Abstract: BackgroundThe purpose of this study was to investigate the radiological and surgical correlation between preoperative magnetic resonance images (MRI) and the intraoperative findings in patients with acquired adult flatfoot.ResultsThe overall radiological–surgical correlation between preoperative MRI and the intraoperative findings for posterior tibial tendon insufficiency was only slight to fair in our patient’s series. Comparing the most commonly used posterior tibial tendon classification systems, the classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…When looking at spring ligament assessment, according to some authors, MRI abnormalities (mostly on the superiormedial bundle) seem to correlate well with operative findings 44,64,65 ; however, recent literature suggests that the concordance may not always be clinically relevant. 7 In our series, MRI accuracy in detecting spring ligament lesions was almost twice that of US (78% vs 42%). This result (as well as for tendon lesions) is probably based on operator dependence in US scanning.…”
Section: Discussionmentioning
confidence: 49%
“…When looking at spring ligament assessment, according to some authors, MRI abnormalities (mostly on the superiormedial bundle) seem to correlate well with operative findings 44,64,65 ; however, recent literature suggests that the concordance may not always be clinically relevant. 7 In our series, MRI accuracy in detecting spring ligament lesions was almost twice that of US (78% vs 42%). This result (as well as for tendon lesions) is probably based on operator dependence in US scanning.…”
Section: Discussionmentioning
confidence: 49%
“…10 The SLC (superomedial and inferomedial calcaneonavicular ligament), interosseous ligament, plantar metatarsal ligaments, and the plantar naviculocuneiform ligament are all involved. 4 The authors also identified that the deltoid complex was commonly involved, in particular the anterior superficial structures of the complex, which showed a strong statistically significant difference in involvement when compared to a control.…”
Section: Discussionmentioning
confidence: 94%
“…Consideration and scrutiny of these structures is now generating significant interest. 1,4,6,14,18,22 The PT is a dynamic secondary stabilizer of the medial column. It strengthens the actions of the medial ligamentous structures.…”
Section: Discussionmentioning
confidence: 99%